Systemic administration of AAV-Slc25a46 mitigates mitochondrial neuropathy in Slc25a46−/− mice. (16th January 2020) - Yang, Li; Slone, Jesse; Li, Zhuo; Lou, Xiaoting; Hu, Yueh-Chiang; Queme, Luis F; Jankowski, Michael P; Huang, Taosheng
Abstract: Mitochondrial disorders are the result of nuclear and mitochondrial DNA mutations that affect multiple organs, with the central and peripheral nervous system often affected. Currently, there is no cure for mitochondrial disorders. Currently, gene therapy offers a novel approach for treating monogenetic disorders, including nuclear genes associated with mitochondrial disorders. We utilized a mouse model carrying a knockout of the mitochondrial fusion–fission-related gene solute carrier family 25 member 46 ( Slc25a46 ) and treated them with neurotrophic AAV–PHP.B vector carrying the mouse Slc25a46 coding sequence. Thereafter, we used immunofluorescence staining and western blot to test the transduction efficiency of this vector. Toluidine blue staining and electronic microscopy were utilized to assess the morphology of optic and sciatic nerves following treatment, and the morphology and respiratory chain activity of mitochondria within these tissues were determined as well. The adeno-associated virus (AAV) vector effectively transduced in the cerebrum, cerebellum, heart, liver and sciatic nerves. AAV– Slc25a46 treatment was able to rescue the premature death in the mutant mice ( Slc25a46 −/− ). The treatment-improved electronic conductivity of the peripheral nerves increased mobility and restored mitochondrial complex activities. Most notably, mitochondrial morphology inside the tissues of both the central and peripheral nervous systems was normalized, and the neurodegeneration, chronic neuroinflammation and loss of Purkinje cell dendrites observed within the mutant mice were alleviated. Overall, our study shows that AAV–PHP.B's neurotrophic properties are plausible for treating conditions where the central nervous system is affected, such as many mitochondrial diseases, and that AAV– Slc25a46 could be a novel approach for treating SLC25A46-related mitochondrial disorders.